Monitoring crustal movements in northern Tianshan Mountain based on GPS technology - A.V. Vilayev (Geodesy and Geodynamics, 2017)
Monitoring results for the period 2009–2014 by ten standard GPS stations allowed to determine the crustal movements of seismically active region in south-eastern Kazakhstan. Maps of movement velocity were made in geocentric coordinate system and in reference system of the Eurasian continent. GPS points displacements reflect the features of modern deformation processes that are notable in the high seismic activity region. The structure of the velocity field divergence qualitatively confirms major deformation in the sublatitudinal direction which is parallel to the main ridge of the northern Tianshan Mountain. The epicenters of earthquakes are in agreement with the border areas of compression–tension, as well as the allocated areas of multidirectional rotary motion. The conclusion is that GPS monitoring of the movements of the Earth's crust can be used to evaluate the territory's stress–strain state for the purpose of seismic zoning and seismic risk assessment.